Trial of Adaptability Competency Training Module to Improve Adaptive Performance for Employees of PT. X - Putra Utama, Joshua Aditya; Riasnugrahani, Missiliana; Gunawan, Gianti (Analitika: Jurnal Magister Psikologi UMA, 2023)
An experimental method was used in this research by employing Adaptability Competency Training Module to improve Adaptive Performance for employees of PT. X. There were 34 respondents for each of the experimental and control groups who participated. Each participant filled out pre-test and post-test, respectively, the Adaptive Performance Scale and The Adaptability Scale which were spaced for seven days. The total Adaptive Performance and the Adaptability Competency means were compared, between pre-test and post-test used Paired Samples T-Test, then between experimental and control groups used Independent Samples T-Test. Based on statistical calculation, total pre-test and post-test scores of the experimental group were significantly differences, with Adaptive Performance coefficient (t=–2.941) and Adaptability Competency coefficient (t=–3.498). Based on these findings, it can be concluded that total Adaptive Performance and Adaptability Competency scores of the participants were significantly increased after being given Adaptability Competency training. To be more effective, future researchers and company authorities can consider this training to be applied on a wider scale and deepen the domain of behavior and results.